Aplikasi Topikal Red Palm Oil (Elaeis Guineensis) Sebagai Adjuvan Scaling Root-Planing pada Gingivitis: Pengaruh terhadap Parameter Klinis dan Kadar Matrix Metalloproteinase-8 Saliva : Sebuah Uji Klinis Acak Terkontrol Tersamar Ganda - Dinda Ratna Juwita; Hirowati Ali; Cimi Ilmiawati (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Gingivitis is an inflammatory condition of the gingiva caused by dental plaque accumulation. Scaling root-planing (SRP) is the gold standard therapy for gingivitis; however, its long-term effectiveness may be limited due to bacterial recolonization and plaque re-accumulation after treatment. Red Palm Oil (RPO) (Elaeis guineensis) contains bioactive compounds with potential as an adjunctive therapy following SRP. Objective: This study aimed to analyze the effect of topical RPO application as an adjunctive therapy after SRP on changes in clinical parameters and salivary Matrix Metalloproteinase-8 (MMP-8) levels in gingivitis patients. Methods: This study utilized a randomized controlled trial design. A total of 40 gingivitis patients were randomly assigned into two groups: the control group (n=20), receiving SRP with placebo application, and the RPO group (n=20), receiving SRP followed by topical RPO application. The evaluated parameters included Gingival Index (GI), Oral Hygiene Index-Simplified (OHI-S), and salivary MMP-8 levels. Statistical analyses were performed using parametric and nonparametric tests according to data distribution. Results: Significant differences in GI and OHI-S changes were observed between the control and RPO groups (p<0.05), with a greater reduction in clinical parameter scores in the RPO group. Analysis of salivary MMP-8 levels showed a decrease after intervention in both groups; however, the difference between groups was not statistically significant (p>0.05). Conclusion: Topical application of Red Palm Oil as an adjunctive therapy after SRP has the potential to improve clinical periodontal parameters in gingivitis patients. However, the additional effect of RPO on changes in salivary MMP-8 levels has not demonstrated a statistically significant difference compared with SRP alone.